Distribuição de resultados em companhias abertas: um estudo sobre os fatores que afetam a decisão de pagar juros sobre capital próprio - Paulo, Maria do Socorro Abreu de (2015)
The use of interest on capital as a form of profit sharing provides tax gains to companies that adopt this form, in lieu of dividends. Given this advantage, it is expected that profitable companies with Income Tax and Social Contribution on Profit payable opt for the payment of Interest on Own Capital. However, research shows that even large companies with shares listed on the Stock Exchange do not adopt this strategy. A possible explanation of this phenomenon is the existence of conflicts of interest between the company and controlling shareholders who would be adversely affected by this type of distribution. This paper investigates whether companies with the best levels of corporate governance are more likely to pay interest on equity, among a sample of 168 of the largest Brazilian companies, with data collected for the years 2010, 2011, 2012 and 2013. Through the use of logistic regression technique, concluded a company with highest level of Corporate Governance has more chance of paying interest on equity than the others, considering the data from the years 2010 to 2013. The same technique applied to 2007 year data pointed in the same direction, but without statistical significance. The research introduces a new approach with regard to the study on the JSCP distribution in Brazil, using as an explanatory variable the level of corporate governance, adding to the findings of previous studies